The Plant that Survived Atomic Explosion, Can it Survive Human Threat? - Chakravarty, Sumit; Rai, Prakash; Puri, Anju; Shukla, Gopal; Pala, Nazir A. (Indian Forester, 2016)
Ginkgo biloba L., the maidenhair tree and a living fossil that survived the first atomic explosion in Japan reminds us with hope of survival. It is the single surviving species of the Order Ginkgoales that has restricted wild distribution in China. The Ginkgo biloba has multitude medicinal, spiritual and horticultural importance worldwide. It is amongst few plant species that have been traditionally or scientifically used and evaluated for their possible medicinal applications. Its usage has been documented in traditional Chinese medicine since 5000 years. Now, it is one of the most widely prescribed herbals or pharmaceuticals in the western world. In spite of its rarity, long reproductive cycle and low rate of natural regeneration, the tree has been exploited indiscriminately due to its high medicinal value, forcing it to face a high risk of extinction. Unfortunately, despite of having huge medicinal properties and ornamental value, the species still has not received much conservation attention. Considering the international importance and conservation value of Ginkgo biloba multi-strategic efforts are required involving all stakeholders. In addition to its in situ and ex situ measures, environmental legislation and government planning is also essential to ensure adequate conservation of this living fossil plant.